How sustainable business model innovation and green technology innovation interact to affect sustainable corporate performance - Zhou, Nan; Pan, Liurong; Tian, Ye; Zhu, Nian; Cai, Xiang; Gao, Jianhua (Frontiers in Environmental Science, 2023)
Sustainable business model innovation (SBMI) and green technology innovation (GTI) are keys to creating shared social and business value, and both are essential elements of responsible innovation. However, SBMI or GTI is unable to develop a sustainable business. The main purpose of this study is to analyze sustainable dual innovation as a conceptual framework based on the panel data of 1468 Chinese manufacturing A-share listed companies from 2010 to 2020, and it has obtained three essential findings. First, there is a significant matching effect between SBMI and GTI on sustainable corporate performance (SCP). Companies report higher levels of SCP when there is a higher congruence in SBMI with GTI. Secondly, organizations with high SBMI-low GTI realize superior SCP compared to organizations with low SBMI-high GTI. The high SBMI-low GTI becomes an ideal choice for most companies and avoids the “destructive factors” brought by low SBMI-high GTI. Finally, a highly aggressive corporate strategy has a “magnifying effect” on the impact of the combination of SBMI and GTI on SCP. The research provides a comprehensive understanding and collective impact of SBMI and GTI on SCP. Overall, findings provide a theoretical basis for enterprises to decide on the consistency/inconsistency trade-off between SBMI and GTI. Moreover, it encourages to enterprises must develop an aggressive strategy to balance.